Magnetic core material, preparation method thereof and high-frequency transformer
By preparing nano-titanium dioxide/hexagonal boron nitride composites and performing surface modification, the problem of poor thermal conductivity of the magnetic core material is solved, and the high thermal conductivity and low loss performance of the magnetic core material in high-frequency transformers are achieved.
Patent Information
- Application Number
- CN202510358249.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-08-12
AI Technical Summary
Existing magnetic core materials have poor thermal conductivity in high-frequency applications, resulting in local heating affecting the life of electronic devices.
By preparing nanotitanium dioxide/hexagonal boron nitride composite material, surface modification is performed by dopamine hydrochloride and polyethyleneimine, FeSiAl magnetic powder is insulated and coated to improve thermal conductivity.
It significantly improves the thermal conductivity of the core material, reduces eddy current loss, and enhances the high-frequency performance and service life of the core.
Smart Images

Figure CN120473273A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnetic materials, and in particular relates to a magnetic core material and a preparation method thereof, and a high-frequency transformer. Background Art
[0002] A transformer is a device that uses the principle of electromagnetic induction to change AC voltage. Depending on the operating frequency, it can be divided into low-frequency transformers and high-frequency transformers. High-frequency transformers can withstand high additional voltages through small excitation currents. Moreover, when the output power is the same, high-frequency transformers are much smaller than low-frequency transformers. Therefore, with the widespread demand for power systems and industrial applications, high-frequency and high-power transformers have been widely used in power electronic circuits.
[0003] Traditional silicon steel sheets and iron powder cores are not suitable for high-frequency applications due to their large eddy current losses. Soft ferrites can adapt well to high-frequency environments, but their saturation magnetic induction intensity is low and cannot meet the requirements of high-power applications. Magnetic powder cores are composite magnetic materials composed of magnetic particles and insulating coating materials. Magnetic powder cores can achieve high magnetic flux density, high resistivity, high magnetic permeability and other properties by regulating material composition and process design, and can meet the magnetic performance requirements of magnetic components in the high-frequency band. The insulating coating can effectively block the contact between powder particles, thereby increasing the resistivity, reducing the eddy current loss of the magnetic powder core, and improving the saturation magnetic induction intensity and resistivity of the magnetic powder core, thereby improving the high-frequency performance of the magnetic powder core.
[0004] In the prior art, magnetic particles have poor thermal conductivity after being insulated and coated, and are prone to local heating in high-frequency applications, which affects the service life of electronic devices. Summary of the Invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a magnetic core material and a preparation method thereof, and a high-frequency transformer. In order to solve the problem of poor thermal conductivity of the magnetic core material, the present invention prepares a nano-titanium dioxide / hexagonal boron nitride composite material, and modifies the surface of the composite material with dopamine hydrochloride and polyethyleneimine, and adds the composite material to an organic silicone resin to perform insulation coating on FeSiAl magnetic powder, thereby improving the thermal conductivity of the FeSiAl magnetic powder.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a magnetic core material, which comprises the following components in parts by weight: 100-120 parts of FeSiAl magnetic powder, 4-6 parts of silicone resin, 10-15 parts of acetone, 2-3 parts of thermally conductive filler, and 1-2 parts of curing agent; the thermally conductive filler is a polyethyleneimine-modified polydopamine-coated nano-titanium dioxide / hexagonal boron nitride composite material.
[0007] Furthermore, the thermal conductive filler is prepared from the following components in parts by weight: 20-30 parts of hexagonal boron nitride, 6-9 parts of titanium trichloride, 10-12 parts of dopamine hydrochloride and 7-9 parts of polyethyleneimine.
[0008] The present invention also provides a method for preparing a magnetic core material, which specifically comprises the following steps: S1, adding hexagonal boron nitride to water, and ultrasonically treating the water to obtain a hexagonal boron nitride dispersion; S2. Hexadecyltrimethylammonium bromide is added to an organic solvent, and the hexagonal boron nitride dispersion prepared in step S1 is added, stirred evenly, and a 15 wt% titanium trichloride solution is added. The mixture is placed in a reactor, reacted at 200-230° C. for 5-8 hours, and the solid is collected, washed, and dried to obtain a nano-titanium dioxide / hexagonal boron nitride composite material. S3. Take the nano-titanium dioxide / hexagonal boron nitride composite material prepared in step S2 and add it to Tris-HCl buffer, adjust the pH value to 8.5, stir evenly, add dopamine hydrochloride and polyethyleneimine and mix evenly, shake in a water bath at 25° C. for 6-8 hours, filter, wash, and dry to obtain a thermal conductive filler; S4. Add silicone resin and curing agent to acetone, add thermal conductive filler, perform ultrasonic treatment to evenly disperse the thermal conductive filler in the silicone resin, add FeSiAl magnetic powder, stir thoroughly, vacuum dry at 60°C, press and mold at 1000-1200 MPa, and perform stress relief annealing at 150-200°C to obtain the magnetic core material.
[0009] Furthermore, in step S1, the amount of hexagonal boron nitride added to water is 30-60 mg / mL.
[0010] Furthermore, in step S1, the ultrasonic treatment is performed at a power of 200-300 W and for 30-40 minutes.
[0011] Furthermore, in step S2, the amount of cetyltrimethylammonium bromide added to the organic solvent is 40 mg / mL.
[0012] Furthermore, in step S2, the organic solvent is a mixed solvent of n-pentanol and n-hexane, and the volume ratio of n-pentanol to n-hexane is 1:6.
[0013] Furthermore, in step S3, the amount of the nano-titanium dioxide / hexagonal boron nitride composite material added to the Tris-HCl buffer is 20-30 mg / mL.
[0014] The present invention also provides a high-frequency transformer, comprising a magnetic core, wherein the magnetic core is selected from the above-mentioned magnetic core materials.
[0015] The beneficial effects achieved by the present invention are as follows: The nano-titanium dioxide / hexagonal boron nitride composite material is modified by using dopamine hydrochloride and polyethyleneimine to enhance the compatibility of the nano-titanium dioxide / hexagonal boron nitride composite material with silicone resin, thereby improving the thermal conductivity of the magnetic core material; Nano-titanium dioxide / hexagonal boron nitride composite materials were prepared by solvothermal method with titanium trichloride and hexagonal boron nitride as raw materials to improve the stability and thermal conductivity of hexagonal boron nitride. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Graph showing thermal conductivity test results of Examples 1-3 and Comparative Examples 1-3 of the present invention; Figure 2 Magnetic loss test results of Examples 1-3 of the present invention; Figure 3 This is a scanning electron microscope image of the thermal conductive filler of Example 1 of the present invention.
[0017] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods and materials similar or equivalent to those described herein can be applied to the present invention. The preferred embodiments and materials described herein are for illustrative purposes only and are not intended to limit the scope of this application.
[0020] In response to the deficiencies in the prior art mentioned in the background technology, the first aspect of the present invention provides a magnetic core material, comprising the following components in parts by weight: 100-120 parts of FeSiAl magnetic powder, 4-6 parts of silicone resin, 10-15 parts of acetone, 2-3 parts of thermally conductive filler and 1-2 parts of curing agent; the thermally conductive filler is a polyethyleneimine-modified polydopamine-coated nano-titanium dioxide / hexagonal boron nitride composite material.
[0021] In some embodiments, the thermally conductive filler is prepared from the following components in parts by weight: 20-30 parts of hexagonal boron nitride, 6-9 parts of titanium trichloride, 10-12 parts of dopamine hydrochloride, and 7-9 parts of polyethyleneimine.
[0022] Among them, the elemental composition of FeSiAl magnetic powder can be 4%-13% Al, 4%-7% Si and the rest Fe, which has the advantages of high saturation magnetic induction intensity and low cost. The silicone resin has good electrical insulation performance and thermal stability. After coating the FeSiAl magnetic powder, the better electrical insulation performance can reduce the eddy current loss of the FeSiAl magnetic powder, so that the FeSiAl magnetic powder has better high-frequency performance. The better thermal stability prevents it from being destroyed by high temperature in subsequent heat treatment.
[0023] Moreover, among thermally conductive fillers, hexagonal boron nitride is a layered crystal with a graphene-like structure. This layered structure enables its theoretical thermal conductivity to reach 3000W / (m·K), and it also has good insulation properties. Using titanium trichloride as a raw material, nano-titanium dioxide can be loaded on the surface of hexagonal boron nitride. Nano-titanium dioxide can act as a spacer between hexagonal boron nitride layers to prevent hexagonal boron nitride from stacking, thereby allowing hexagonal boron nitride to maintain a layered geometric form and improve the stability of hexagonal boron nitride. In addition, nano-titanium dioxide can act as a bridge between the layers of hexagonal boron nitride, reducing the thermal resistance between hexagonal boron nitride and improving the thermal conductivity of hexagonal boron nitride. Dopamine can self-polymerize to form polydopamine in an alkaline environment. Polydopamine has good adhesion and can adhere to the surface of nano-titanium dioxide / hexagonal boron nitride composite materials. Polydopamine contains functional groups such as phenolic hydroxyl groups and amino groups, which can further undergo Michael addition and Schiff base reactions with other molecules. Therefore, by using polydopamine as a modification medium and grafting polyethyleneimine on the surface of the composite material, a certain number of amino groups can be introduced on the surface of the composite material to increase the dispersibility of the composite material in the silicone resin, increase the compatibility of the composite material with the silicone resin, reduce the thermal resistance between the composite material and the silicone resin, and improve the thermal conductivity of the composite material.
[0024] A second aspect of the present invention provides a method for preparing a magnetic core material, which specifically comprises the following steps: S1. Add hexagonal boron nitride to water and perform ultrasonic treatment to obtain a hexagonal boron nitride dispersion; S2. Hexadecyltrimethylammonium bromide is added to an organic solvent, and the hexagonal boron nitride dispersion prepared in step S1 is added, stirred evenly, and a 15 wt% titanium trichloride solution is added. The mixture is placed in a reactor, reacted at 200-230° C. for 5-8 hours, and the solid is collected, washed, and dried to obtain a nano-titanium dioxide / hexagonal boron nitride composite material. S3. Take the nano-titanium dioxide / hexagonal boron nitride composite material prepared in step S2 and add it to Tris-HCl buffer, adjust the pH value to 8.5, stir evenly, add dopamine hydrochloride and polyethyleneimine and mix evenly, shake in a water bath at 25° C. for 6-8 hours, filter, wash, and dry to obtain a thermal conductive filler; S4. Add silicone resin and curing agent to acetone, add thermal conductive filler, perform ultrasonic treatment to evenly disperse the thermal conductive filler in the silicone resin, add FeSiAl magnetic powder, stir thoroughly, vacuum dry at 60°C, press and mold at 1000-1200 MPa, and perform stress relief annealing at 150-200°C to obtain the magnetic core material.
[0025] It should be noted that the hexagonal boron nitride dispersion can form an oil-in-water emulsion with the help of hexadecyltrimethylammonium bromide and an organic solvent, and then Ti is introduced through titanium trichloride. 3+ The ions act as titanium sources and grow into nano-titanium dioxide on hexagonal boron nitride through electrostatic attraction.
[0026] In some embodiments, in step S1, the amount of hexagonal boron nitride added to water is 30-60 mg / mL.
[0027] In some embodiments, in step S1, the ultrasonic treatment is performed at a power of 200-300 W and for a time of 30-40 minutes.
[0028] In some embodiments, in step S2, the amount of cetyltrimethylammonium bromide added to the organic solvent is 40 mg / mL.
[0029] In some embodiments, in step S2, the organic solvent is a mixed solvent of n-pentanol and n-hexane, and the volume ratio of n-pentanol to n-hexane is 1:6.
[0030] In some embodiments, in step S3, the amount of the nano-titanium dioxide / hexagonal boron nitride composite material added to the Tris-HCl buffer is 20-30 mg / mL.
[0031] A third aspect of the present invention provides a high-frequency transformer, comprising a magnetic core, wherein the magnetic core is selected from the magnetic core materials mentioned above.
[0032] The present invention will be further described below by way of specific embodiments.
[0033] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified. Example
[0034] A magnetic core material is prepared by including the following components in parts by weight: 100 parts of FeSiAl magnetic powder, 4 parts of silicone resin, 10 parts of acetone, 2 parts of thermally conductive filler, and 1 part of curing agent; the thermally conductive filler is prepared by including the following components in parts by weight: 20 parts of hexagonal boron nitride, 6 parts of titanium trichloride, 10 parts of dopamine hydrochloride, and 7 parts of polyethyleneimine.
[0035] The method for preparing the magnetic core material specifically comprises the following steps: S1. Add hexagonal boron nitride to water at an amount of 30 mg / mL and ultrasonicate at a power of 200 W for 30 minutes to obtain a hexagonal boron nitride dispersion. S2. Take hexadecyltrimethylammonium bromide and add it to an organic solvent. The amount of hexadecyltrimethylammonium bromide added to the organic solvent is 40 mg / mL. The hexagonal boron nitride dispersion prepared in step S1 is added and stirred evenly. A 15 wt % titanium trichloride solution is added and placed in a reactor. The reaction is carried out at 200° C. for 5 hours. The solid is collected, washed, and dried to obtain a nano-titanium dioxide / hexagonal boron nitride composite material. S3. Take the nano-titanium dioxide / hexagonal boron nitride composite material prepared in step S2 and add it to Tris-HCl buffer at an amount of 20 mg / mL, adjust the pH value to 8.5, stir evenly, add dopamine hydrochloride and polyethyleneimine and mix evenly, shake in a water bath at 25° C. for 6 hours, filter, wash, and dry to obtain a thermal conductive filler; S4. Add silicone resin and curing agent to acetone, add thermal conductive filler, and perform ultrasonic treatment to uniformly disperse the thermal conductive filler in the silicone resin. Add FeSiAl magnetic powder, stir thoroughly, vacuum dry at 60°C, press into shape at 1000 MPa, and perform stress relief annealing at 150°C to obtain a magnetic core material. Example
[0036] A magnetic core material is prepared by including the following components in parts by weight: 120 parts of FeSiAl magnetic powder, 6 parts of silicone resin, 15 parts of acetone, 3 parts of thermally conductive filler, and 2 parts of curing agent; the thermally conductive filler is prepared by including the following components in parts by weight: 30 parts of hexagonal boron nitride, 9 parts of titanium trichloride, 12 parts of dopamine hydrochloride, and 9 parts of polyethyleneimine.
[0037] The method for preparing the magnetic core material specifically comprises the following steps: S1. Add hexagonal boron nitride to water at an amount of 60 mg / mL and ultrasonicate at a power of 300 W for 40 minutes to obtain a hexagonal boron nitride dispersion. S2. Take hexadecyltrimethylammonium bromide and add it to an organic solvent. The amount of hexadecyltrimethylammonium bromide added to the organic solvent is 40 mg / mL. The hexagonal boron nitride dispersion prepared in step S1 is added and stirred evenly. A 15 wt % titanium trichloride solution is added and placed in a reactor. The reaction is carried out at 230° C. for 8 hours. The solid is collected, washed, and dried to obtain a nano-titanium dioxide / hexagonal boron nitride composite material. S3. Take the nano-titanium dioxide / hexagonal boron nitride composite material prepared in step S2 and add it to Tris-HCl buffer at an amount of 30 mg / mL, adjust the pH value to 8.5, stir evenly, add dopamine hydrochloride and polyethyleneimine and mix evenly, shake in a water bath at 25° C. for 8 hours, filter, wash, and dry to obtain a thermally conductive filler; S4. Add silicone resin and curing agent to acetone, add thermal conductive filler, and perform ultrasonic treatment to uniformly disperse the thermal conductive filler in the silicone resin. Add FeSiAl magnetic powder, stir thoroughly, vacuum dry at 60°C, press into shape at 1200 MPa, and perform stress relief annealing at 200°C to obtain a magnetic core material. Example
[0038] A magnetic core material is prepared by including the following components in parts by weight: 110 parts of FeSiAl magnetic powder, 5 parts of silicone resin, 13 parts of acetone, 2.5 parts of thermally conductive filler, and 1.5 parts of curing agent; the thermally conductive filler is prepared by including the following components in parts by weight: 25 parts of hexagonal boron nitride, 7 parts of titanium trichloride, 11 parts of dopamine hydrochloride, and 8 parts of polyethyleneimine.
[0039] The method for preparing the magnetic core material specifically comprises the following steps: S1. Add hexagonal boron nitride to water at a concentration of 45 mg / mL and ultrasonicate at a power of 250 W for 35 minutes to obtain a hexagonal boron nitride dispersion. S2. Take hexadecyltrimethylammonium bromide and add it to an organic solvent. The amount of hexadecyltrimethylammonium bromide added to the organic solvent is 40 mg / mL. The hexagonal boron nitride dispersion prepared in step S1 is added and stirred evenly. A 15 wt % titanium trichloride solution is added and placed in a reactor. The reaction is carried out at 220° C. for 7 hours. The solid is collected, washed, and dried to obtain a nano-titanium dioxide / hexagonal boron nitride composite material. S3. Take the nano-titanium dioxide / hexagonal boron nitride composite material prepared in step S2 and add it to Tris-HCl buffer at an amount of 25 mg / mL, adjust the pH value to 8.5, stir evenly, add dopamine hydrochloride and polyethyleneimine and mix evenly, shake in a water bath at 25° C. for 7 hours, filter, wash, and dry to obtain a thermal conductive filler; S4. Add silicone resin and curing agent to acetone, add thermal conductive filler, and perform ultrasonic treatment to uniformly disperse the thermal conductive filler in the silicone resin. Add FeSiAl magnetic powder, stir thoroughly, vacuum dry at 60°C, press into shape at 1100 MPa, and perform stress relief annealing at 170°C to obtain a magnetic core material.
[0040] Comparative Example 1 This comparative example provides a magnetic core material, which differs from Example 1 only in that unmodified hexagonal boron nitride is used to replace the thermal conductive filler in the composition, and the other components and component contents are the same as those in Example 1.
[0041] Comparative Example 2 This comparative example provides a magnetic core material, which differs from Example 1 only in that titanium trichloride is not included in the components of the thermal conductive filler, and the remaining components and component contents are the same as those in Example 1.
[0042] Comparative Example 3 This comparative example provides a magnetic core material, which differs from Example 1 only in that the thermal conductive filler does not include dopamine hydrochloride and polyethyleneimine, and the remaining components and component contents are the same as those in Example 1.
[0043] Experimental Example 1 The thermal conductivity of the magnetic core materials of Examples 1-3 of the present invention and Comparative Examples 1-3 was tested as follows: a sample was taken, the sample density (ρ) was measured, and the thermal diffusivity (α) of the sample was measured using an LFA467 laser thermal conductivity meter. The specific heat capacity (C) was obtained by comparing the sample with a standard sample. The thermal conductivity (λ) of the sample was calculated using the following formula: λ = α·ρ·C, in units of W / (m·K).
[0044] Figure 1 This is a graph of thermal conductivity test results. As shown in the figure, the thermal conductivities of Examples 1-3 are 8.531 W / (m·K), 8.264 W / (m·K), and 8.361 W / (m·K), respectively. The thermal conductivities of Comparative Examples 1-3 are 3.724 W / (m·K), 7.185 W / (m·K), and 6.087 W / (m·K), respectively. The thermal conductivity of Example 1 is increased by 229% compared with Comparative Example 1. It can be seen that compared with directly adding hexagonal boron nitride, the thermal conductive filler prepared in Example 1 can greatly improve the thermal conductivity of the magnetic core material.
[0045] Experimental Example 2 The magnetic core materials of Examples 1-3 of the present invention were subjected to magnetic loss testing. The specific method is as follows: using a MATS-3000S soft magnetic material measuring device, 0.5 mm enameled copper wire, 10 turns of the primary coil and 15 turns of the secondary coil, the magnetic loss was measured at 50 mT and 50-1000 kHz.
[0046] Figure 2 Magnetic loss test results are shown in the figure. As shown in the figure, the losses of the magnetic core materials of Examples 1-3 at 1000kHz are 10.62W / kg, 11.36W / kg, and 9.84W / kg, respectively. The losses at 50kHz are 0.18W / kg, 0.21W / kg, and 0.19W / kg, respectively. It can be seen that the magnetic core materials of Examples 1-3 have smaller high-frequency losses and are suitable for high-frequency transformers.
[0047] Experimental Example 3 The morphology of the thermal conductive filler of Example 1 of the present invention was observed using a scanning electron microscope.
[0048] Figure 3 This is a scanning electron microscope image of the thermal conductive filler. As shown in the figure, the surface of the thermal conductive filler is relatively rough due to the polyethyleneimine grafted on the surface.
[0049] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, and all of these should be included in the scope of the claims of the present invention.
Claims
1. A magnetic core material, characterized in that: The invention comprises the following components in parts by weight: 100-120 parts of FeSiAl magnetic powder, 4-6 parts of silicone resin, 10-15 parts of acetone, 2-3 parts of thermal conductive filler and 1-2 parts of curing agent; the thermal conductive filler is a polyethyleneimine-modified polydopamine-coated nano-titanium dioxide / hexagonal boron nitride composite material.
2. The magnetic core material according to claim 1, characterized in that: The thermal conductive filler is prepared from the following components in parts by weight: 20-30 parts of hexagonal boron nitride, 6-9 parts of titanium trichloride, 10-12 parts of dopamine hydrochloride and 7-9 parts of polyethyleneimine.
3. A method for preparing a magnetic core material according to claim 1, characterized in that: The specific steps include: S1, adding hexagonal boron nitride to water, and ultrasonically treating the water to obtain a hexagonal boron nitride dispersion; S2. Hexadecyltrimethylammonium bromide is added to an organic solvent, and the hexagonal boron nitride dispersion prepared in step S1 is added, stirred evenly, and a 15 wt% titanium trichloride solution is added. The mixture is placed in a reactor, reacted at 200-230° C. for 5-8 hours, and the solid is collected, washed, and dried to obtain a nano-titanium dioxide / hexagonal boron nitride composite material. S3. Take the nano-titanium dioxide / hexagonal boron nitride composite material prepared in step S2 and add it to Tris-HCl buffer, adjust the pH value to 8.5, stir evenly, add dopamine hydrochloride and polyethyleneimine and mix evenly, shake in a water bath at 25° C. for 6-8 hours, filter, wash, and dry to obtain a thermal conductive filler; S4. Add silicone resin and curing agent to acetone, add thermal conductive filler, perform ultrasonic treatment to evenly disperse the thermal conductive filler in the silicone resin, add FeSiAl magnetic powder, stir thoroughly, vacuum dry at 60°C, press and mold at 1000-1200 MPa, and perform stress relief annealing at 150-200°C to obtain the magnetic core material.
4. The method for preparing a magnetic core material according to claim 3, wherein: In step S1, the amount of hexagonal boron nitride added to water is 30-60 mg / mL.
5. The method for preparing a magnetic core material according to claim 3, wherein: In step S1, the ultrasonic treatment is performed at a power of 200-300 W and for 30-40 minutes.
6. The method for preparing a magnetic core material according to claim 3, wherein: In step S2, the amount of cetyltrimethylammonium bromide added to the organic solvent is 40 mg / mL.
7. The method for preparing a magnetic core material according to claim 3, wherein: In step S2, the organic solvent is a mixed solvent of n-pentanol and n-hexane.
8. The method for preparing a magnetic core material according to claim 7, wherein: In the mixed solvent, the volume ratio of n-pentanol to n-hexane is 1:
6.
9. The method for preparing a magnetic core material according to claim 2, wherein: In step S3, the amount of the nano-titanium dioxide / hexagonal boron nitride composite material added to the Tris-HCl buffer is 20-30 mg / mL.
10. A high-frequency transformer, comprising a magnetic core, characterized in that: The magnetic core is selected from the magnetic core material according to claim 1.